#TITLE_ALTERNATIVE# - MAHARANI (NIM : 10211007), JUWITA
As human population growth in Indonesia, the need of energy recources is increased. Therefore an alternative and renewable energy is needed, like the geothermal energy. In this thesis, Geoelectric method used to find out the prospect area of geothermal. Principle of this method is injecting some electric current to the subsurface through current electrode. The data which obtained from the measurement results are apparent resistivity and depth of measurement. To obtained the real resistivity data, there are some method which is used in this thesis, those are inverse modeling which consist of forward modeling problem with finite element discretization in a block matrix resistivity. Then used the ABIC method which is contain smoothness-constrain factor to minimize discourtesy of resistivity value. The modeling of the data generated in the form of resistivity values which can represent the actual resistivity at any given distance and depth. After that, the data would be interpreted by using surfer8 program. The result of that is distribution of resistiviy in the form of 2-D contour. From the result of the data interpretation, Just a fewer sounding points that have low resistivity zone range of 1 Ωm - 30 Ωm. Those low resistivity zone have predictable contain geothermal zone.